Acute and chronic effects of the short-chain chlorinated paraffins on the monogonont rotifer Brachionus manjavacas revealed by multi-biomarker determination - Jaehee Kim; Seong Duk Do; Jae-Sung Rhee (Ecotoxicology and Environmental Safety)
Short-chain chlorinated paraffins (SCCPs) are persistent organic pollutants of global concern. Despite their presence in low concentrations in aquatic environments, the detrimental effects of SCCPs on zooplankton remain limited. In this study, we evaluated the potential effects of acute and chronic exposure (24 h and 10 days) to various concentrations of SCCPs, including 1/10 NOEC, NOEC, and LC10, as retrieved from a 24-h toxicity experiment, using the monogonont rotifer Brachionus manjavacas. A dose-dependent increase in mortality was measured, with an LC50 value of 132 μg L−1 after 24 h. Treatment to the 24h-LC10 value significantly elevated intracellular content of reactive oxygen species, in addition with a marked elevation in malondialdehyde level. Glutathione levels were elevated following exposure to the 24-h LC10 value, along with the induction of enzymatic activities of crucial antioxidant components, including glutathione S-transferase, glutathione peroxidase, glutathione reductase, catalase, and superoxide dismutase. Chronic exposure to the NOEC value over 10 days resulted in hazardous effects on survival, lifespan, reproduction, and population maintenance in B. manjavacas. Taken together, SCCPs induced acute toxicity in rotifers primarily through the induction of oxidative stress. Even at sub-lethal concentrations, consistent exposure can lead to significant detrimental effects throughout the life cycle, indicating that SCCPs pose a serious threat to the sustainability of rotifer populations.